Shifting alliance dynamics in the Indo-Pacific: Is the Taiwan question going regional? - Gaens Bart; Mattlin Mikael (Ulkopoliittinen instituutti, 2026)
Heightened tensions surrounding the Taiwan question are lending urgency to efforts to revitalise the 75-year-old US network of alliances and security partnerships in the Indo-Pacific region. The more proactive role of Japan is not to China’s liking.